2014
DOI: 10.1111/jsm.12570
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of the Neuroregenerative Peptide Galanin in the Major Pelvic Ganglion Following Cavernous Nerve Injury

Abstract: Introduction Erectile dysfunction (ED) remains a frequent complication of radical prostatectomy due to injury to the cavernous nerves (CNs). A recent microarray showed the neuropeptide galanin to be one of the most strikingly upregulated genes in the rat major pelvic ganglion (MPG) after bilateral CN crush injury (BCNI). Aim The aim of this study is to evaluate the temporal regulation of galanin in the MPG after BCNI and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…We also found many fluorescent DRG neurons (Figure ), a result consistent with the notion that galanin accumulation in pseudo‐unipolar neuron somas reaches a peak after birth (Marti et al, ) then decreasing to low levels in the adult (Xu, Shi, & Hökfelt, ). Interestingly, galanin expression in the ganglia can be markedly upregulated after injury (Xu et al, ), a phenomenon also occurring in the autonomic nervous system (Weyne et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found many fluorescent DRG neurons (Figure ), a result consistent with the notion that galanin accumulation in pseudo‐unipolar neuron somas reaches a peak after birth (Marti et al, ) then decreasing to low levels in the adult (Xu, Shi, & Hökfelt, ). Interestingly, galanin expression in the ganglia can be markedly upregulated after injury (Xu et al, ), a phenomenon also occurring in the autonomic nervous system (Weyne et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, the galanin knock-out postnatal mice showed significantly increase in the number of apoptotic cells in a subset of dorsal root ganglion neurons at postnatal day 3-4 as compared with wild controls (Holmes et al, 2000). Lastly, it has been demonstrated that galanin can promote regeneration of neurons, including proliferation and migration of cells in the peripheral and central nervous system (Vrontakis, 2002;Weyne et al, 2014). Approximate one-third of neurite out growth in dorsal root ganglion cultures is dependent on the tonic release of galanin in the adult rats after peripheral nerve injury (Holmes et al, 2000).…”
Section: Roles Of Galanin In Exercise Protection and Exercise Trauma mentioning
confidence: 95%
“…It has been demonstrated that galanin can promote proliferation, migration, nutrition, and regeneration of neurons in the peripheral and central nervous systems after injury (Vrontakis, ; Wilson‐Gerwing and Verge, ; Weyne et al, ). Approximately one‐third of neurite outgrowth in DRG cells was dependent on the galanin release after injury of the peripheral nerve in adult rats (Holmes et al, ).…”
Section: Galanin Boosts Repair Of Exercise‐induced Somatic Damagementioning
confidence: 99%
“…It has been demonstrated that galanin can promote proliferation, migration, nutrition, and regeneration of neurons in the peripheral and central nervous systems after injury (Vrontakis, 2002;Wilson-Gerwing and Verge, 2006;Weyne et al, 2014). Approximately one- (Holmes et al, 2000).…”
Section: Peripheral Nervous Systemmentioning
confidence: 99%